In situ alignment of graphene nanoplatelets in poly(vinyl alcohol) nanocomposite fibers with controlled stepwise interfacial exfoliation. Issue 7 (21st May 2019) - Xu, Weiheng; Jambhulkar, Sayli; Verma, Rahul; Franklin, Rahul; Ravichandran, Dharneedar; Song, Kenan
Abstract : Exfoliated and aligned continuous graphene nanoplatelet channels with enhanced mechanical properties and superior electrical conductivity. Abstract : Hierarchically microstructured tri-axial poly(vinyl alcohol)/graphene nanoplatelet (PVA/GNP) composite fibers were fabricated using a dry-jet wet spinning technique. The composites with distinct PVA/GNPs/PVA phases led to highly oriented and evenly distributed graphene nanoplatelets (GNPs) as a result of molecular chain-assisted interfacial exfoliation. With a concentration of 3.3 wt% continuously aligned GNPs, the composite achieved a ∼73.5% increase in Young's modulus (∼38 GPa), as compared to the pure PVA fiber, and an electrical conductivity of ∼0.38 S m −1, one of the best mechanical/electrical properties reported for polymer/GNP nanocomposite fibers. This study has broader impacts on textile engineering, wearable robotics, smart sensors, and optoelectronic devices.